The requirements of dry fertilizer placement in direct drilled crops by improved chisel coulter : a thesis ... for the degree of Master of Philosophy in Agricultural Mechanisation at Massey University, Palmerston North - Choudry, Muhammad Afzal (Massey University, 1981)
This study was conducted to evaluate the effects of dry fertiliser placement as a function of design criteria for direct drills. The study was conducted in three parts. 1. Rectangular turf blocks (140 × 140 × 200 mm) of undisturbed soil were taken from a Tokomaru concretionery silt loam soil, site of permanent pasture. Seed and fertiliser placement was achieved by removing 2.5 mm diameter soil cores at 20% (d.b.) soil moisture content. Ammonium sulphate (21-0-0) was applied at the rate of 60 kg N haˉ¹. It was either mixed with rape seed (Brassica napus L. c. Tower) or separated from the seed by 10 or 20 mm of soil, horizontally or vertically. A control treatment had no fertiliser. Where seed and fertiliser were mixed or separated vertically by a 10 mm soil core, seedling emergence was reduced significantly (P < 0.01) compared to control. Where separated horizontally by either 10 or 20 mm of soil, or vertically by 20 mm of soil emergence counts were similar to no fertiliser placement. Initiation of emergence was significantly (P <0.05) more rapid with 20 mm separation than with only 10 mm or no separation (mixed) of seed and fertiliser. Maximum seedling emergence counts were significantly (P < 0.05) delayed when seed and fertiliser were either mixed or horizontally separated by 10 mm or vertically separated by 10 or 20 mm. Horizontal separation of fertilizer by 20 mm from seed produced significantly more height, weight and total yield than the mixed or 10 mm placements, harvested 5 weeks after sowing (P <0.05). 2. An improved chisel coulter was used for drilling rape seed with simultaneous fertiliser placement in cultivated and uncultivated Tokomaru silt loam soil under field conditions. Ammonium sulphate (75kg-N haˉ¹) was placed along with the seed, horizontally separated by 20mm of soil. Significantly greater plant populations(P <0.01) were obtained with direct drilled plots compared to plots cultivated a week before drilling. This trend was more pronounced at lower soil moistures (19-20% db) at the time of drilling than higher ones (23-37%). 3. Direct drilling of large turf blocks (1.8 m × 660 mm × 200 mm) was carried out in the laboratory using both the improved chisel coulter and the modified version. The blocks were extracted from the same pasture as in 1 above. Horizontal and vertical placements of ammonium sulphate and mono-ammonium phosphate fertilisers at 20mm from the rape seed and at rates of either 30 or 60 kg-N haˉ¹ largely resulted in higher germination and fewer dead seeds compared to mixed seed and fertiliser placements. Placements of fertiliser in wet soil and horizontal placements in dry soil tended to produce higher germination percentages and fewer viable seeds. The interaction of fertiliser × placement indicated that mono-amnonium phosphate (16-9-0) mixed with rape seed was likely to cause more dead seeds than at 20mm placement. It appears from the results of these 3 experiments that the horizontal separation of fertiliser by 20mm from rape seed was desirable from the point of view of germination, seedling emergence, initiation of emergence, delay in maximum seedling emergence and yield characteristics of plants. With this fertiliser placement arrangement plant populations in uncultivated soil were greater (up to 30%) than in cultivated soil. The improved direct drilling chisel coulter was capable of achieving this fertiliser placement objective without modification.
Keywords: Drills (Planting machinery); Fertilizer spreaders